Pengaruh Komunikasi Mengajar Guru Pendidikan Agama Kristen Terhadap Minat Belajar Siswa Kelas X TKR SMK Negeri 2 Siatas Barita Tapanuli Utara Tahun 2023/2024 - Liha Sari Nadeak; Dorlan Naibaho; Frainskoy Rio Naibaho; Lince R.T Simamora; Roida Lumbanttobing (Publisher STPKat, 2024)
The aim of this research is to determine the influence of Christian Religious Education Teachers' Teaching Communication on Learning Interest of Class X TKR Students at SMK Negeri 2 Siatas Barita North Tapanuli in 2023/2024. The research method used is a descriptive quantitative method. The population was all 101 students of class X TKR SMK Negeri 2 Siatas Barita who were Christians and a sample of 50 people was determined using random sampling techniques. Data was collected using a positive closed questionnaire with 35 items, namely 16 items for variable Siatas Barita North Tapanuli 2023/2024, proven through the following data analysis: 1) Test analysis requirements: a) positive relationship test obtained rxy = 0.469 > rtable(a=0.05,n=50) = 0.297. b) Testing a significant relationship obtained tcount= 3.680 > ttable(a=0.05, dk=n-2=48)= 2.021. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y ̂=